Perspectives From Patients and Care Providers on the Management of Fecal Incontinence: A Needs Assessment. Issue 4 (April 2017) - Helewa, Ramzi M.; Moloo, Husein; Williams, Lara; Foss, Kristine M.; Baksh-Thomas, Waheeda; Raiche, Isabelle
Abstract : BACKGROUND: A large proportion of Canadians experience fecal incontinence, with no avenue for effective treatments. The Ottawa Hospital has recently started a percutaneous tibial nerve stimulation program for patients who have not improved with conservative efforts. OBJECTIVE: As part of this program implementation, a qualitative needs assessment was undertaken to better define successful outcomes and to identify barriers for program sustainability. DESIGN: This was a cross-sectional, qualitative study involving standardized, semistructured interviews. SETTINGS: The study was conducted at a single tertiary care center. PATIENTS: Patients experiencing fecal incontinence, as well as nurses, physical therapists, and physicians, were enrolled in the study. MAIN OUTCOME MEASURES: Interview questions revolved around success definitions, barriers, and promoters of fecal incontinence care. Transcripts were analyzed to develop themes surrounding fecal incontinence care. RESULTS: Twelve interviews were undertaken raising a total of 17 different themes. Barriers to fecal incontinence care included education for both the care provider and patients. Access issues for treatments were also highlighted. Promoters of fecal incontinence care were reflected by the impact that it has on quality of life, personal hygiene, psychological burden, and activity and productivity. The definition of fecal incontinence success was focused on improvements in quality of life rather than a numerical reduction of incontinence episodes. LIMITATIONS: This study was limited in its small number of interviews conducted. We were unable to identify patients who were unable to seek out care for fecal incontinence. CONCLUSIONS: Patient and care provider education surrounding fecal incontinence is lacking. Furthermore, access for effective treatments is a real barrier for Canadians experiencing fecal incontinence. Programs should focus on improvement of overall quality of life rather than a reduction of incontinence episodes.